2012
DOI: 10.2174/157488712800100233
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Treatment of Depressive Disorders: A Review of Evidence-Based Treatment Options

Abstract: In summary, using a hierarchical approach, it was possible to assign different levels of evidence to the various treatment options for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Kaufman and colleagues (2013), who analyzed data from a large representative psychiatric epidemiological study among AIs in two reservation communities, found that depression was related to family, cultural, or community dynamics—most likely all three – which has implications for treatment considerations for depression in AI individuals. Treatment interventions that address interpersonal relationships and family dynamics may be effective in treating depression that is related to family factors (Dirmaier et al, 2012; Brakemeir & Frase, 2012). Culturally rooted and community developed means to address mental health conditions have significant potential to improve health (Gone, 2013; Kirmayer, Simpson, & Cargo, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman and colleagues (2013), who analyzed data from a large representative psychiatric epidemiological study among AIs in two reservation communities, found that depression was related to family, cultural, or community dynamics—most likely all three – which has implications for treatment considerations for depression in AI individuals. Treatment interventions that address interpersonal relationships and family dynamics may be effective in treating depression that is related to family factors (Dirmaier et al, 2012; Brakemeir & Frase, 2012). Culturally rooted and community developed means to address mental health conditions have significant potential to improve health (Gone, 2013; Kirmayer, Simpson, & Cargo, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ineffectiveness of the treatment in some patients or intolerability to the side effects, a large number of patients do not comply with the treatment and search for other therapeutic options [13, 31, 35]. Hence, increasing number of people with depressive symptoms explored other nonpharmacological interventions including psychotherapy and counseling, psychoeducation, exercise, problem solving therapy, guided self-help and behavioral activation treatments [36], or even complementary and alternative medicine (CAM) [3, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving therapy can improve psychological outcomes in individuals with mental health disorders (e.g. depression) (Dirmaier et al, 2012), spinal cord injury (Dorstyn et al, 2011), parents of children with chronic illness (Eccleston et al, 2012), and cancer patients (Allen et al, 2002; Nezu et al, 2003). …”
Section: Introductionmentioning
confidence: 99%